Pendidikan Anak Usia Dini Berpedoman dengan Psikologi Islam - Ade Rabiah Nasution; Iffatul Fauza; Mirna Wati; Nurul Aini; Nashran Azizan (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
The purpose of this observe is to give an explanation for early adolescence schooling based on Islamic psychology and understand infant psychology and conduct primarily based at the concept of monotheism via a mixture of knowledge and perception. Islamic psychology is a shape of psychology which is primarily based specially at the description of Muslim people who have clear distinctiveness and this conduct is a mirrored image in their stories within the interaction of the arena and the religious surroundings with the intention and goal of improvement. Islamic first-class. The health of spiritual existence and the happiness of the afterlife in Islamic education lays the foundation of the Qur'an for the desires and coaching substances of Islamic education, particularly Islamic education. getting to know is done through exciting and applicable methods to obtain the predicted desires of Islamic training in Indonesia. The studies used in this paintings is library research and makes use of a important descriptive approach that emphasizes the ability to investigate records via textual content and principle. The outcomes of literature studies and the remark that kids are satisfactory seeds can encompass primary human values. however in next developments the human soul is no longer stable. Western education has a tendency to overemphasize intelligence (cognitive) and ignore mental (affective) functions. Islamic psychology is gift in the world of early childhood training as a brand new paradigm that views people as a whole and intact. children now not most effective recognize standard principles but additionally Islamic ideas about humans and feature the bodily and intellectual capacity to forge a near courting between the 2. so as for kids to come to be best human beings, they deal with nature, protect it and look at the commandments of God.